PERAN ASEAN TOURISM FORUM DALAM MENINGKATKAN KUNJUNGAN WISATAWAN ASING KE FILIPINA TAHUN 2015-2017 - Arya Purnama; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to describe the roles of ASEAN in escalating the tourists visits in Philippines especially in 2015 to 2017. With the ASEAN Tourism Forum (ATF), all ASEAN member countries use it as a forum to achieve the national interests countries, as well as Philippines. Philippines uses ATF as a forum that facilitates to promote domestic tourism. Philippines is a country that has tourism potential and has a dynamic but relatively good rate of foreign tourist arrivals.This research theoretically has built by using pluralism perspective on International Relations and supported international organizational theory. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative methods. ASEAN Tourism Forum plays an important role in the development of regional tourism. ATF is a step of regional cooperation in order to promote ASEAN as one of the best international tourism destinations. ASEAN Tourism Forum has positives impact on the development of the Philippine tourism industry in terms of escalating foreign tourist arrivals in the Philippines. Keywords : ATF, Destinations, Foreign Tourist Arrivals